Biodata mining (BioMed Central, 2008)
Open access, peer reviewed, online journal encompassing research on all aspects of data mining applied to high-dimensional biological and biomedical data, focusing on computational aspects of knowledge discovery from large-scale genetic, transcriptomic, genomic, proteomic, and metabolomic data.
Keywords: Bioinformatics : Periodicals; Computational biology : Periodicals; Data mining : Periodicals; Computational Biology; Data Mining; Biomedicine; Bioinformatics; Computational biology; Data mining; Biology - General